2010
DOI: 10.1144/0016-76492009-072
|View full text |Cite
|
Sign up to set email alerts
|

The generation and evolution of the continental crust

Abstract: The continental crust is the archive of the geological history of the Earth. Only 7% of the crust is older than 2.5 Ga, and yet significantly more crust was generated before 2.5 Ga than subsequently. Zircons offer robust records of the magmatic and crust-forming events preserved in the continental crust. They yield marked peaks of ages of crystallization and of crust formation. The latter might reflect periods of high rates of crust generation, and as such be due to magmatism associated with deep-seated mantle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
283
4
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 684 publications
(302 citation statements)
references
References 132 publications
12
283
4
3
Order By: Relevance
“…Previous research has indicated that zircons with δ 18 O values of b6.5‰ may not form from supracrustal melts, whereas zircons with δ 18 O values of N 6.5‰ are indicative of the significant involvement of supracrustal materials (e.g., Cavosie et al, 2005;Davidson et al, 2005;Valley et al, 2005;Hawkesworth and Kemp, 2006;Kemp et al, 2006;Fu et al, 2009;Hawkesworth et al, 2010;Lu et al, 2013). Although some of the PDL zircon δ 18 O values obtained in this study are higher than 6.5‰ (n = 28 of 159, Appendix C; Fig.…”
Section: Crustal Contamination Of Partial Melts From Mantle or Mantlecontrasting
confidence: 44%
“…Previous research has indicated that zircons with δ 18 O values of b6.5‰ may not form from supracrustal melts, whereas zircons with δ 18 O values of N 6.5‰ are indicative of the significant involvement of supracrustal materials (e.g., Cavosie et al, 2005;Davidson et al, 2005;Valley et al, 2005;Hawkesworth and Kemp, 2006;Kemp et al, 2006;Fu et al, 2009;Hawkesworth et al, 2010;Lu et al, 2013). Although some of the PDL zircon δ 18 O values obtained in this study are higher than 6.5‰ (n = 28 of 159, Appendix C; Fig.…”
Section: Crustal Contamination Of Partial Melts From Mantle or Mantlecontrasting
confidence: 44%
“…It has been recognised for some time that the volume of continental crust was substantial in the early Archaean (see review by Hawkesworth et al, 2010), but to date it has been unclear how continental freeboard controlled the amount of emergent continental landmasses. Continental freeboard depends more on mantle temperature, crustal composition, and continental hypsometry (also temperature-dependent) than on the growth of continental crust.…”
Section: Iron Formations Primary Productivity and Atmospheric Oxygementioning
confidence: 99%
“…The term "juvenile" refers to crustal material that plots on or close to the depleted mantle evolution line, suggesting derivation from a depleted mantle source. In contrast, "reworked" refers to the remobilization of preexisting crust by partial melting and/or erosion and sedimentation (25,26). Complete sample information, methodology, and geochemical datasets (U-Pb, Lu-Hf, and komatiite) are available in the Supporting Information, Figs.…”
mentioning
confidence: 99%